Biodegradable Metals - Eli Aghion (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The interest in biocompatible and biodegradable metals, such as magnesium, is mainly related to their potential use as structural material for orthopedic and cardiovascular applications where a temporary medical device is required. However, in the case of magnesium, in vivo experiments have clearly shown that the corrosion degradation rate of magnesium and its alloys is too high and, hence, results in producing gas cavities that can promote the danger of gas embolism, tissue separation, and premature loss of mechanical integrity. The aim of this Special Issue on Biodegradable Metals is to explore and introduce innovative strategies to overcome the current limitations of magnesium.